CSR: Perception V/S Reality - Saluja, Prerna Dawar (Journal of Advanced Research in Humanities and Social Sciences, 2021)
CSR is an obligation and responsibility of corporations towards society to serve different areas such as poverty, education, employment etc. CSR is where a company recognizes the society in which it exists and attempts to benefit it in same way. The research is empirical in nature and is based on primary and secondary data. Primary data, which is collected by survey through an online questionnaire and secondary data is based on observations. Random sampling method of data collection is used for collecting primary data and the responses of 50 respondents are analyzed. Some of our findings are based on secondary data which shows that Lego, Microsoft and Google are among the top three companies majorly contributing to the areas of corporate social responsibility. How to cite this article:  Saluja PD. CSR: Perception V/S Reality. J Adv Res Humani Social Sci 2020; 7(4): 1-5.